Domain 2 of non-structural protein 5A (NS5A) of hepatitis C virus is natively unfolded - Liang, Yu (2012)
Nonstructural protein 5A protein (NS5A) of hepatitis C virus (HCV) plays an important role in the regulation of viral replication, interferon resistance, and apoptosis. HCV NS5A comprises three domains. Recently the structure of domain 1 has been determined, revealing a structural scaffold with a novel zinc-binding motif and a disulfide bond. At present, the structures of domains 2 and 3 remain undefined. Domain 2 of HCV NS5A (NS5A-D2) is important for functions of NS5A and involved in molecular interactions with its own NS5B and PKR, a cellular interferon-inducible serine/threonine specific protein kinase. In this study we performed structural analysis of domain 2 by multinuclear nuclear magnetic resonance (NMR) spectroscopy. The analysis of the backbone 1H, 13C, and 15N resonances, 3JHNα coupling constants ,and 3D NOE data indicates that NS5A-D2 lacks secondary structural elements and reveals characteristics of unfolded proteins. NMR relaxation parameters confirmed the lack of rigid structure in the domain. The absence of an ordered conformation and the observation of a highly dynamic behavior of NS5A-D2 may provide an underlying molecular basis on its physiological function to allow NS5A-D2 to interact with a variety of biological partners.